Pemanfaatan Media Digital dalam Pembelajaran Pendidikan Agama Islam untuk Meningkatkan Literasi Keagamaan Siswa Sekolah Menengah Atas - Hengki Satrisno; Maryam Maryam; Isti Hawa; Nadia Dwitama; Melita Dwi Aprianti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2025)
The development of digital technology has brought significant changes in the world of education, including in Islamic Religious Education (PAI) learning. This study aims to describe the use of digital media in PAI learning and its efforts to improve religious literacy of high school students. This study used a qualitative descriptive method with a case study approach, involving PAI teachers and 11th grade students. Data collection techniques included observation, interviews, and documentation, while data analysis was conducted using content analysis and triangulation of sources and methods to ensure the validity of the information. The results showed that the use of digital media, such as interactive videos, e-learning modules, and online quiz applications, can increase student engagement and understanding of religious material, both from the cognitive, affective, and psychomotor aspects. Digital media also encourages students to seek additional information independently and develop critical thinking skills. Technical obstacles such as limited devices and internet connections can be overcome through a hybrid strategy and teacher guidance. This research provides a practical contribution to the development of technology-based PAI learning strategies that are adaptive, interactive, and improve students' religious literacy.